Analisis Usaha Orang Asli Papua di Distrik Abepura Kota Jayapura di Sektor Usaha Mikro atau Kecil Perdagangan - Flora Hosio, Yakomina (Green Publisher Indonesia, 2024)
Businesses of Indigenous Papuans which are not recorded by the Jayapura City Government Entrepreneurship Program are unable to compete in the small business or micro trade sector. This study is based on the affirmation of Indigenous Papuan (OAP) traders. Collection techniques and using interviews and literature study. The results of the research show that empowerment programs that cannot be accepted by small or micro businesses belonging to OAP can be carried out by collecting data to take part in entrepreneurship training. And the solution is to prohibit non-Papuans from selling products and garden products that have Papuan socio-cultural characteristics to provide opportunities for OAP to develop in the micro or small trade business sector. The Jayapura City Government carries out strengthening through data collection and then provides entrepreneurship training by intellectuals in the form of entrepreneurial competencies in order to gain access to capital from the regional government and even carries out promotions with creative economic products which must be developed for empowerment with the principle of taking sides with OAP in accordance with the Special Autonomy Law based on the Regional Regulation.